Regulation and quality evaluation system for HIV diagnostics in China. Issue 2 (March 2016) - Xu, Sihong; Huang, Weijin; Zhang, Li; An, Juanjuan; Li, Xiuhua; Song, Aijing; Nie, Jianhui; Zhang, Chuntao; Wang, Youchun
Abstract: A sophisticated regulatory framework has been constructed for Human immunodeficiency virus (HIV) diagnostics in China, which have developed over the past 30 years. China National Institutes for Food and Drug Control acts as the legal institution in this regulatory framework, launching important activities to ensure the quality of HIV diagnostics. These include the analysis of the main problems faced in developing domestic HIV diagnostics, by investigating the quality of HIV diagnostics and their development; exploring the key factors affecting the quality of HIV diagnostics, to determine the criteria for screening national reference samples; the development of new technologies and methods for preparing reference samples; and the establishment of nine types of national reference panels and nine national standards to evaluate the quality of HIV diagnostics. Based on these researches, a quality evaluation system was established, including nine types of national reference panels, nine national standards for HIV diagnostics, and five sample banks (HIV-positive sample bank, HIV-negative sample bank, common international genotype sample bank, seroconversion series sample bank, HIV virus bank) to evaluate the quality of HIV diagnostics in China. The regulatory framework and the quality evaluation system are pivotal in ensuring the quality of the HIV diagnostics licensed in China.